Zeigen die schweizerischen Messungen eine Gefährdung der Ozon-Schicht? - Johannes Staehelin; Hans U. Dütsch (CHIMIA)
The world’s longest continous series of measurements of total atmospheric ozone (over 60 years) and the most extensive record of« Umkehrmeasurements» (over 30 years) containing information on the vertical structure of the atmospheric ozone has been performed at Arosa. The Swiss record of ozone balloon measurements reaching the middle stratosphere also includes more than 20 years of observations. – The total ozone measurements of Arosa show a clearly negative trend since about 1970 with a decrease of about 4% during the period from 1969 to 1988. – The current knowledge of the chemistry of the stratosphere is discussed taking into account the mechanisms of chain reactions initiated by anthropogenic pollutants reaching the stratosphere, such as chlorofluoro- and bromofluorocarbon compounds and dinitrogen oxide. Also the transport processes explaining the dependence of the stratospheric ozone on season and altitude are briefly discussed. – The information on the ozone-trends at different altitudes strongly supports the theory of the beginning destruction of the ozone shield in the planetary atmosphere by anthropogenic activities. However, there is some indication, that changes in the hemispheric stratospheric circulation also contributed to the observed ozone decrease. These findings are finally compared with the results of the Ozone Trends Panel, which are based on the work of more than 100 scientists and use a combination of satellite and ground based data.